The low-dose CHK1 inhibitor prexasertib triggers VDAC1 dephosphorylation to activate mtDNA-STING signaling and synergize immunotherapy - Yu Fu; Xiaoyan Kang; Wenting Li; Zanhong Wang; Wanwan Luo; Bin Yang; Yaoyuan Cui; Funian Lu; Tianyu Qin; Xingyuan Hu; Jingjing Yin; Xi Li; et al. (Cell Reports)
Summary: CHK1 inhibitors exhibit dose-limiting toxicity despite potent tumor cytotoxicity in clinical trials. Here, we reveal that low-dose prexasertib induces mtDNA damage by impairing repair machinery, triggering cytosolic mtDNA release via VDAC1 to activate STING-mediated innate immunity. Mechanistically, prexasertib blocks CHK1 phosphorylation and competitively recruits Nek1 kinase, thereby activating the ATR/CHK1 signaling cascade. Consequently, it disrupts the phosphorylation of VDAC1 by Nek1 kinase at T107 and promotes the formation of VDAC1 oligomers, where mtDNA exits. In vivo, low-dose prexasertib exhibits immune-modulatory effects and synergizes safely with immune checkpoint blockade at subtherapeutic doses. Our findings establish reduced-dose CHK1 inhibition as a strategy to amplify immunotherapy efficacy while circumventing systemic toxicity, providing a translatable framework for optimizing therapeutic windows in clinical oncology.